SYSTEMATIC LITERATURE REVIEW: PENGARUH GROWTH MINDSET TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Irawan, Dede; Syamsuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of growth mindset on students' mathematical communication skills mediated by affective factors, namely self-efficacy, learning motivation, self-confidence, and learning independence. Employing a Systematic Literature Review (SLR) method, 15 relevant scholarly articles published between 2021–2025 from Google Scholar were analyzed, adhering to stringent inclusion and exclusion criteria to ensure relevance to mathematics education. Literature synthesis reveals that growth mindset positively impacts these affective factors, which in turn enhance students' mathematical communication abilities, including articulating ideas orally and in writing, linking concrete concepts to symbolic representations, and formulating conjectures and generalizations. Students with a growth mindset exhibit greater persistence, receptivity to constructive feedback, intrinsic motivation, and learning independence, thereby improving the efficacy of their mathematical communication. Integrating growth mindset strategies into mathematics curricula is recommended to address Indonesia's low PISA 2022 mathematics score of 366.